PENGARUH MIGRASI MASUK DAN UPAH MINIMUM TERHADAP TINGKAT PENGANGGURAN DI KOTA PEKANBARU TAHUN 2000 - 2014 - Juliyanti Maria Marpaung; Lapeti Sari; Eriyati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how much influence the amount of migration in and the minimum wage on unemployment in the city of Pekanbaru years 2000-2014. This study is used quantitative research methods and using multiple linear regression. Results of the research by using multiple regression analysis known and simultaneous regression test (Test F) note that Fhitung is 6,080 and Ftable is 3.89 and the degree of probability (sig.) is 0.015 at 5% ( 0,05 )confidence level. It is thus known that Fhitung> Ftable (6.080> 3.89) shows that migration in and minimum wage simultaneously has effect and no significant effect on the unemployment rate in the city of Pekanbaru. Partial regression test (ttest) indicates that the variable-migration to have a positive relationship and have no significant effect while the minimum wage has a negative relationship and significant effect on the unemployment rate Pekanbaru years 2000-2014. The magnitude of the effect that the (R2) is 0.503, which means that the unemployment rate as the dependent variable is able to be explained by the independent variables named migration in and the minimum wage by 50.3% and the remaining 49.7% is explained by variables - variables other than research.Keyword : migration in, minimum wage and unemployment rate